European Crohn's and Colitis Organisation Topical Review on Treatment Withdrawal ['Exit Strategies'] in Inflammatory Bowel Disease. (2nd August 2017) - Doherty, Glen; Katsanos, Konstantinos H; Burisch, Johan; Allez, Matthieu; Papamichael, Konstantinos; Stallmach, Andreas; Mao, Ren; Berset, Ingrid Prytz; Gisbert, Javier P; Sebastian, Shaji; Kierkuś, Jarosław; Lopetuso, Loris; et al.
Abstract: Clinically effective therapies now exist for remission maintenance in both ulcerative colitis [UC] and Crohn's Disease [CD]. For each major class of IBD medications [5-aminosalicyclates, immunomodulators, and biologic agents], used alone or in combination, there is a risk of relapse following reduction or cessation of treatment. A consensus expert panel convened by the European Crohn's and Colitis Organisation [ECCO] reviewed the published literature and agreed a series of consensus practice points. The objective of the expert consensus is to provide evidence-based guidance for clinical practice so that physicians can make informed decisions in partnership with their patients. The likelihood of relapse with stopping each class of IBD medication is reviewed. Factors associated with an altered risk of relapse with withdrawal are evaluated, and strategies to monitor and allow early identification of relapse are considered. In general, patients in clinical, biochemical, and endoscopic remission are more likely to remain well when treatments are stopped. Reintroduction of the same treatment is usually, but not always, successful. The decision to stop a treatment needs to be individualized, and shared decision making with the patient should take place.